Frequency and geographical distribution of genotypes and mating types of Cryptococcus neoformans and Cryptococcus gattii species complexes in Argentina - Taverna, Constanza Giselle (2020)
Fil: Taverna, CG. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas; Argentina.